Genome Structure of the Symbiont Bifidobacterium pseudocatenulatum CECT 7765 and Gene Expression Profiling in Response to Lactulose-Derived Oligosaccharides - Benítez-Páez, Alfonso; Moreno, F. Javier; Sanz, María L.; Sanz, Yolanda (Frontiers in Microbiology, 2016)
Bifidobacterium pseudocatenulatum CECT 7765 was isolated from stools of a breast-fed infant. Although this strain is generally considered an adult-type bifidobacterial species, it has also been shown to have pre-clinical efficacy in obesity models. In order to understand the molecular basis of its adaptation to complex carbohydrates and improve its potential functionality, we have analyzed its genome and transcriptome, as well as its metabolic output when growing in galacto-oligosaccharides derived from lactulose (GOS-Lu) as carbon source. B. pseudocatenulatum CECT 7765 shows strain-specific genome regions, including a great diversity of sugar metabolic-related genes. A preliminary and exploratory transcriptome analysis suggests candidate over-expression of several genes coding for sugar transporters and permeases; furthermore, five out of seven beta-galactosidases identified in the genome could be activated in response to GOS-Lu exposure. Here, we also propose that a specific gene cluster is involved in controlling the import and hydrolysis of certain di- and tri-saccharides, which seemed to be those primarily taken-up by the bifidobacterial strain. This was discerned from mass spectrometry-based quantification of different saccharide fractions of culture supernatants. Our results confirm that the expression of genes involved in sugar transport and metabolism and in the synthesis of leucine, an amino acid with a key role in glucose and energy homeostasis, was up-regulated by GOS-Lu. This was done using qPCR in addition to the exploratory information derived from the single-replicated RNAseq approach, together with the functional annotation of genes predicted to be encoded in the B. pseudocatenulatum CETC 7765 genome.